(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2013)
A Dutch architect Cosman Citroen (1881-1935) was one of the most remarkable architects in the Netherlands Indies. He left his position in Amsterdam and then went to Surabaya to be an advisory architect of the Municipality of Surabaya. During his career in the city, he designed many buildings and constructions so that any discussion about Dutch colonial architecture in the city cannot be separated from his works. This article explains from which family he came, how situation of Surabaya when he arrived, and what his activities other than as the Municipal architect.